“Pest Forests”, “Utility Forests” and “Cow Bends” - Gerard A. Persoon (Revue d'ethnoécologie)
Small and scattered patches of forests contrast sharply within the context of the flat and monotonous dark green pastures in the Dutch polder landscapes. These patches, with various types of trees, are like little islands, surrounded by ditches. They are not remnants of the original old peat swamp forests but farmers created the patches in the past for particular purposes. Their names offer clear indications: in addition to the general name of ‘small polder forests’ (polderbosjes) they are called ‘pest forests’ (pestbosjes or krengenbosjes, places where contaminated or dead animals were dumped), ‘farmers’ utility or coppice forests’ (boerengeriefhoutbosjes or hakhoutbosjes, from which farmers collected all types of useful wood), or ‘cow bends or milk forests’ (koebochten or melkbosjes, places where the cows were milked and where the manure could be collected). With the modernization of agriculture and alternative sources of energy, many of these forest islands have been cleared for the sake of expanding the pastures. However, increasingly these forest patches are also viewed from a different perspective. Nowadays they are valued as an important element in the country’s (agri)cultural heritage, but also for the role they play in terms of the polders’ biodiversity (flora as well as fauna), which has rapidly declined with the modernization of agriculture in recent decades. In this article an overview will be given of the origin of these ‘forest islands’ and how they have functioned in the Dutch polder landscape in the past century as an often ignored aspect of farmers’ knowledge and practices. Attention will also be paid to the present efforts to maintain these forest islands.